2011
DOI: 10.1029/2010jd015505
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of recent water vapor continuum measurements upon longwave and shortwave radiative transfer

Abstract: [1] Recent measurements of the water vapor continuum have been combined to form an empirical continuum termed the BPS continuum model. This covers the 800 to 7500 cm −1 spectral region for the self continuum and most of the major absorbing spectral regions between 240 and 7300 cm −1 for the foreign continuum. Longwave (i.e., absorption/emission of terrestrial radiation between 1 and 3000 cm −1 ) and shortwave (i.e., using solar radiation as a source and considering atmospheric absorption between 1000 and 17000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 35 publications
1
70
0
2
Order By: Relevance
“…The water vapor continuum is well understood to play an important role in determining the longwave cooling rates of water vapor in the atmosphere [e.g., Clough et al ., ; Schwarzkopf and Ramaswamy , ; Collins et al ., ]. Numerous studies [ Mlawer and Clough , ; Ptashnik et al ., , , ; Paynter and Ramaswamy , , ] have suggested that the continuum will also increase the absorption of solar radiation by the atmosphere. For example, Paynter and Ramaswamy [] showed that the water vapor continuum could result in between 1.1 W m −2 and 3.2 W m −2 additional clear‐sky absorption of solar radiation globally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The water vapor continuum is well understood to play an important role in determining the longwave cooling rates of water vapor in the atmosphere [e.g., Clough et al ., ; Schwarzkopf and Ramaswamy , ; Collins et al ., ]. Numerous studies [ Mlawer and Clough , ; Ptashnik et al ., , , ; Paynter and Ramaswamy , , ] have suggested that the continuum will also increase the absorption of solar radiation by the atmosphere. For example, Paynter and Ramaswamy [] showed that the water vapor continuum could result in between 1.1 W m −2 and 3.2 W m −2 additional clear‐sky absorption of solar radiation globally.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we investigate the impact of the shortwave water vapor continuum upon a GCM's (global climate model) climate simulation by adding the BPS‐MTCKD [ Paynter and Ramaswamy , , ] parameterization of the continuum to the Geophysical Fluid Dynamics Laboratory (GFDL) shortwave radiation code between 2000 and 20,000 cm −1 . BPS‐MTCKD is a version of MTCKD 2.5 that we have altered based upon measurement data in much of the 0–9000 cm −1 spectral region.…”
Section: Introductionmentioning
confidence: 99%
“…The longwave stream is computed over 19 spectral intervals from 10 to 4000 cm −1 . We only consider absorption by H 2 O, with the correlated k coefficients calculated for a pressure grid from 10 bar to 0.01 mb with successive pressure levels following log10(P1/P2) = 0.1, and a temperature grid from 100 to 500 K with ∆T = 25 K. Furthermore, we have implemented a new water vapor continuum parameterization, following the formalism of Paynter and Ramaswamy (2011). This continuum treatment is derived from laboratory measurements taken at temperatures appropriate for atmospheres expected near the inner edge of the habitable zone, and is stronger than the commonly used MT-CKD continuum.…”
Section: Radiative Transfermentioning
confidence: 99%
“…Burch, 1982Burch, , 1985Burch and Alt, 1984). Thus, a validation of the amplitude and of the temperature-dependence of the MT_CKD continuum in those spectral ranges is highly desirable not only to quantify its impact on the estimated radiative budget of the Earth (Held and Soden, 2000;Ptashnik et al, 2011a;Paynter and Ramaswamy, 2011, 2014 but also on the extension of the habitable zone around stars (Kasting et al, 1993;Kopparapu et al, 2013;Leconte et al, 2013a, b;Forget and Leconte, 2014).…”
Section: Introductionmentioning
confidence: 99%